Pengaruh Gaya Kepemimpinan, Sistem Reward, dan Punishment Terhadap Kinerja Karyawan - Said, Umar; Baskara, Ika (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This research aims to analyze the influence of leadership style, reward and punishment systems on employee performance. This research method uses a quantitative approach with the SPSS version 26 analysis tool, and a causal associative approach is used to understand the cause-and-effect relationship between the variables studied. The sample consisted of 91 employees. The results of research on the partial T test show that leadership style does not have a significant influence on employee performance. Likewise, the reward system variable also does not have a significant influence on performance, because it exceeds the specified significance value limit. However, the punishment variable has a significant influence on employee performance. Meanwhile, the results of the simultaneous F test show that leadership style, reward and punishment systems together have a significant influence on employee performance. These results may indicate that these factors can influence employee performance collectively. This research provides important insights for management in managing employees and improving organizational performance.